The social care bottleneck: a strategic analysis of A&E wait time reduction - Kieran Kejiou (Future Healthcare Journal)
Introduction: The NHS is experiencing a shortage of acute medical capability relative to growing demand,1 widely understood to be multifactorial in origin.2 However, this view limits opportunity for targeted solutions. This exploratory study aimed to apply strategic analysis techniques from the business sector to the NHS to identify supply chain inefficiencies and suggest strategic solutions. Methods: NHS England data from an index month of May 2024 were retrospectively analysed. Value chain and situation analyses were conducted to evaluate the ability of the NHS to meet demand. Process flow analysis was used to identify bottlenecks in patient flow through acute hospitals via accident and emergency (A&E) departments. Finally, capital budgeting analysis was conducted to assess the financial feasibility of potential solutions. Results and discussion: Process flow analysis showed that A&E waiting times lengthened by over 4 h while waiting for hospital beds (Fig 1), ultimately influenced by a bottleneck of delayed discharges (Fig 2). Of these, 65% were due to social care shortages or interfacing difficulties.3Vertical integration refers to the corporate-level strategy of combining entities along the value chain. This results in monetary savings by eliminating transaction costs, improving interfaces and co-locating resources. Vertical integration of social care into the NHS may prevent >48% of delayed discharges, while also preventing unnecessary admissions and improving long-term economic productivity. The initial upfront investment would be £3 trillion for integrating non-residential care and £52 trillion for both non-residential and residential care, equating to 6- and 100-times the total Gross Domestic Product of the UK. Long-term, using indefinite growth modelling, both strategies are predicted to result in positive net present values (£16.4 trillion and £5,504,914 trillion, respectively), representing overall savings across the NHS. This assumes that residential care remains revenue-generating. However, the astronomical initial costs would require a more gradual investment strategy to nationalise the social care sector.Limitations of the study include the use of national data, which may mask local trends and socioeconomic disparities between regions; focus on supply-side factors, given that rising demand also contributes to shortages; and the use of data from the index month of May 2024 only. Further analysis is warranted to establish whether the social care bottleneck is seasonal, consistent or anomalous. Conclusions: Vertically integrating social care into the NHS may increase acute medical bed availability, reduce A&E waiting times and thereby improve patient outcomes. However, further research is needed locally and regionally to determine their optimal degrees of integration; and nationally to determine the optimal rate of investment and the consistency of the bottleneck. Further, this must form part of a multifaceted approach to bolster supply and control demand to ensure a sustainable NHS.